Cytological and biochemical markers of autophagy in wheat suspension culture cells under abiotic stress - A.B. Mazina; S.A. Dmitrieva; A.G. Renkova; J.N. Valitova; V.R. Khabibrakhmanova; F.V. Minibayeva (Учёные записки Казанского университета: Серия Естественные науки)
Autophagy is a highly conserved process of intracellular degradation of damaged, oxidized or excess macromolecules and organelles in eukaryotic cells. Under optimal conditions, the baseline level of autophagy is low. However, the activity of autophagic processes greatly increases in response to stress. In this paper, we analyzed the biochemical characteristics of autophagosomes that are formed in the wheat suspension culture cells in response to starvation and as a result of treatment with polyamine spermine. High activity of acid phosphatase and protease, the marker enzymes of lytic vesicles, and changes in the lipid composition were observed in the autophagosomes isolated from the sucrose-deficient cells. It was revealed that polyamine spermine can induce аutophagy, which was accompanied with the changes in the cellular redox status and the energy status of mitochondria. The spermine-induced autophagosomes were characterized by the high enzymatic activity of acid phosphatase and protease. The results obtained suggest the functional universality of the main biochemical markers of autophagosomes in plant cells.